Applications of Blockchain Technology in Logistics and Supply Chain Management—Insights from a Systematic Literature Review - Moritz Berneis; Devis Bartsch; Herwig Winkler (Logistics)
The most successful applications of Blockchain Technology are still in the area of crypto-currencies, although both scientists and practitioners have discovered the potential of Blockchain Technology in Supply Chain Management. There is a significant theoretical literature on Blockchain Technology, but there exists a lack of published case studies and concrete examples. This paper discusses whether this shortcoming is due to insufficient added value of the technology and identifies other possible reasons. Furthermore, this paper introduces Blockchain Technology, describes the origins of Bitcoin, the structure and core properties of the Blockchain, and examines smart contracts. A comprehensive and structured literature analysis identifies concepts for the use of Blockchain Technology in logistics in terms of economic benefits. Additionally, a cluster analysis regarding the topics of the relevant literature was conducted. One finding of the study is that Blockchain Technology is particularly worthwhile for goods with a high value. Moreover, if the trade volume of the respective goods is low, the advantages of BCT are maximized. At the same time, the demand for transparency and immutability of data must be more important than the protection of sensitive data. In addition to concrete use cases of Blockchains, an exemplary logistics process will be presented within the Luxury Supply Chain, showing the advantages of Blockchain Technology for each individual process step.